Influence of Media Outlook and Advertising on Dietary Behaviours of Female Students - Emeka, Ebele Cynthia (Education and Development Research, 2025)
The study focused on Influence of Media Outlook and Advertising on Dietary Behaviors of Female Students in Nwafor Orizu College of Education. The researcher formulated five research purposes and five corresponding research questions. The study adopted a descriptive survey research design. The area of the study was Nwafor Orizu College of Education Nsugbe, Anambra State. The population of the study was comprising of 1901 female Students of the institution. The sampling technique used was multistage random sampling techniques and a sample size of 200 respondents was selected for this study. Instrument used for data collection was a structured questionnaire. The data collected were analyzed using statistical mean and standard deviation. The results indicate that Media Outlook and Advertising significantly influence the dietary behaviors of female students, with a strong emphasis on promoting healthy food choices. The findings also identified the need for nutrition and media literacy education and critical thinking skills to help female students navigate the complex media landscape and make informed dietary choices as one of the strategies towards improving the media influence on dietary behavior. This Study contributes to the existing literature on the impact of media on dietary behaviors and highlights the importance of promoting healthy food habits via media influence among female students in NOCEN.